Protokolle des Ministerrates der Zweiten Republik der Republik Österreich. Kabinett Leopold Figl I, 20. Dezember 1945 bis 8. November 1949. Band 14; ENDERLE-BURCEL et al., PÖM Zweite Republik, Kabinett Figl I, Bd. 14 4. Jänner 1949 bis 21. Februar 1949. Bearbeitung: Elisabeth Gmoser, Peter Melichar, Stefan Semotan - Enderle-Burcel, Gertrude; Mueller, Wolfgang; Wohnout, Helmut (Die Protokolle des Ministerrates der Zweiten Republik Österreich, 2023)
The edition of the minutes of the cabinet meetings of Leopold Figl's first government is an important contribution to the history of the early years of Austria's Second Republic and its political components after World War II. Vol. 14 encompasses meetings no. 139 of January 4, 1949 to no. 146 of February 21, 1949, as well as the accompanying minutes of the Wirtschaftliches Ministerkomitee (Economic Committee of Ministers). The discussions cover matters of foreign, domestic and economic policy, reconstruction, and relations between the Austrian government and the four great powers. Particularly prominent are the pervasive problem of securing basic levels of nutrition for the Austrian population, the ongoing State Treaty negotiations, and measures to implement the European Recovery Program.